2020
DOI: 10.21203/rs.3.rs-136350/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Factors Associated With Risky Sexual Behaviour Amongst Students at a Training College in Limpopo Province, South Africa

Abstract: Background: Globally students who attend colleges indulge in risky sexual practices which in turn expose them to sexually transmitted infections. Risky sexual practices such as multiple sexual partners, unprotected sex, and transactional sex continue to pose risks of sexual transmitted infections, unwanted pregnancy as well as increased termination of pregnancy amongst young people. Engaging in risky sexual behaviour is associated with various factors. Therefore, the reported study was aimed at describing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…This study has established that the association between MSPs and contextual factors has been reflected in many previous studies [16,17,20]. Family support is of special importance to young people, especially at the community-level in many provinces in South Africa, where youth congregate.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…This study has established that the association between MSPs and contextual factors has been reflected in many previous studies [16,17,20]. Family support is of special importance to young people, especially at the community-level in many provinces in South Africa, where youth congregate.…”
Section: Discussionmentioning
confidence: 54%
“…For individual-level factors, the results showed that age was significantly associated with MSP for both female and male young people. For instance, the odds of young females and males aged (20-24 years) had significantly increased odds of having MSP (OR = 6.32, 95% CI: 5.29-7.54 and OR = 6.99, 95% CI: 5.33-9.18, respectively), compared with those (15)(16)(17)(18)(19). Considering educational attainment, the odds of having MSP were 3.6 and 1.6 times higher among female and male young people who had attained a higher education, compared with those with primary or less education.…”
Section: Multilevel Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, mitigating the material risks faced by female students and the associated mental health outcomes will require upskilling them in basic personal finance management [63]. For some students, challenges relating to the late payment of NSFAS bursary funds contribute to young women's engagement in risky sexual behaviours as a coping strategy while waiting to receive the funds [66]. This suggests that the government's provision of bursaries without addressing financial management skills, broader structural inequalities, and poverty faced by the previously disadvantaged Black African population will not directly benefit students in higher education.…”
Section: Discussionmentioning
confidence: 99%